Geometric and electronic properties of graphene-related systems : chemical bonding schemes /: chemical bonding schemes. (2018) - Tran, Ngoc Thanh Thuy; Lin, Shih-Yang; Lin, Chiun-Yan; Lin, Ming-Fa
No abstract available